Collaborative learning with world coffee: an experience from this partner in the classroom (Research, Society and Development, 2020)
Through the World Café teaching strategy, this work aimed to know as a contribution of this strategy, guided by Collaborative Learning, in the teaching of entrepreneurship, in a class of specialization in Management of Micros and Small Businesses of the Federal Institute of Education, Science and Technology Sul-rio-grandense - IFSul, campus Lajeado. The theoretical basis is based on Brown and Isaacs (2007); Demo (1996); Dillenbourg (1999); Bacich and Moran (2017); Torres and Irala (2014). The approach used was qualitative, being the instrument for collecting and creating analyzes prepared by students. As a result, it should be noted that a partnership between World Coffee guided by Collaborative Learning has met this objective, generating ideas without context, enabling students to build knowledge on how to learn to relax, collaborate and use. Thus, it is concluded that the experiences were positive with regard to the involvement and integration of groups of students, or that they contributed to the knowledge about entrepreneurship, approached in this way.